Oligopolistic Price Leadership and Mergers: The United States Beer Industry - Miller, Nathan H.; Sheu, Gloria; Weinberg, Matthew C. (American Economic Review, 2021)
We study a repeated game of price leadership in which a firm proposes supermarkups over Bertrand prices to a coalition of rivals. Supermarkups and marginal costs are recoverable from data on prices and quantities using the model’s structure. In an application to the beer industry, we find that price leadership increases profit relative to Bertrand competition by 17 percent in fiscal years 2006 and 2007, and by 22 percent in 2010 and 2011, with the change mostly due to consolidation. We simulate two mergers, which relax binding incentive compatibility constraints and increase supermarkups. These coordinated effects arise even with efficiencies that offset price increases under Bertrand competition. (JEL G34, K21, L13, L14, L41, L66)